2020
DOI: 10.1099/ijsem.0.004096
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus salinus sp. nov., isolated from commercial solar salt

Abstract: The GenBank accession numbers for the 16S rRNA gene sequence and the whole-genome sequence of strain HMF5848 T are MH454613 and RWIV00000000, respectively. Three supplementary figures are available with the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…Further chemotaxonomic characterization indicated that strain MHSD28 T had menaquinone (MK-7) as the sole respiratory quinone, and the cell-wall peptidoglycan had meso -diaminopimelic acid. These characteristics are congruent with those of numerous Bacillus species [11, 45–47]. The major polar lipids detected comprised diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol (Fig.…”
Section: Full-textsupporting
confidence: 85%
See 1 more Smart Citation
“…Further chemotaxonomic characterization indicated that strain MHSD28 T had menaquinone (MK-7) as the sole respiratory quinone, and the cell-wall peptidoglycan had meso -diaminopimelic acid. These characteristics are congruent with those of numerous Bacillus species [11, 45–47]. The major polar lipids detected comprised diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol (Fig.…”
Section: Full-textsupporting
confidence: 85%
“…The major polar lipids detected comprised diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol (Fig. S8), similar to those of members of the genus Bacillus [11,47,48], further supporting its affiliation with the genus. Moreover, strain MHSD28 T was distinguished from other Bacillus species by the presence of a lipid, aminophospholipid, aminoglycolipid, two phospholipids and five aminolipids (Fig S8).…”
supporting
confidence: 54%